2015
DOI: 10.1038/srep13253
|View full text |Cite
|
Sign up to set email alerts
|

Single-photon decision maker

Abstract: Decision making is critical in our daily lives and for society in general and is finding evermore practical applications in information and communication technologies. Herein, we demonstrate experimentally that single photons can be used to make decisions in uncertain, dynamically changing environments. Using a nitrogen-vacancy in a nanodiamond as a single-photon source, we demonstrate the decision-making capability by solving the multi-armed bandit problem. This capability is directly and immediately associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 36 publications
0
85
0
Order By: Relevance
“…The TOW bombe can also be implemented on the basis of quantum physics. In fact, the authors have exploited optical energy transfer dynamics between quantum dots and single photons to design decision-making devices [25][26][27][28]. Our method might be applicable to a class of problems derived from CBP and broader varieties of game payoff tensors, implying that wider applications can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…The TOW bombe can also be implemented on the basis of quantum physics. In fact, the authors have exploited optical energy transfer dynamics between quantum dots and single photons to design decision-making devices [25][26][27][28]. Our method might be applicable to a class of problems derived from CBP and broader varieties of game payoff tensors, implying that wider applications can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…By "function" here we mean "the emergence of various selectable physical aspects resulting from certain non-trivial processes" -a phenomenon stemming from its relation to the environment system. With this definition in mind we argue that "intelligence" can be defined as "finding the value in having alternative options and choosing the consequence of function" [8] [9] [10]. Following these academic works, our research suggests that aesthetics is a type of function that emerges when the function's conditions are fulfilled [11].…”
Section: Methods Of Researchmentioning
confidence: 99%
“…The "morphism raising a complex one level higher" R P [1] incorporating a wave-shaped arrow is a characteristic morphism (arrow) of the long exact sequence depicted in diagram (8). The formation of a triangular scheme of complexes is called a triangulated category, and while it changes the "histories" it is a simple and clear way to represent the evolving but structure-preserving object(s).…”
Section: Triangulated Category and Octahedron Structurementioning
confidence: 99%
“…Furthermore, Aono et al showed that the satisfiability problem (SAT), which is known to be one of the most important NP-complete problems, can be solved [14]. Naruse et al also demonstrated solving MAB by using single photons emitted from a nanodiamond [17]. Meanwhile, Kasai et al succeeded experimentally in solving CSP based on solid-state electrical circuits on the basis of spatiotemporal dynamics involving noise sources [18].…”
Section: Introductionmentioning
confidence: 96%